Pharmacokinetic Properties of Memantine after a Single Intraperitoneal Administration and Multiple Oral Doses in Euploid Mice and in the Ts65Dn Mouse Model of Down's Syndrome. Issue 5 (10th July 2017) - Victorino, Daniella B.; Bederman, Ilya R.; Costa, Alberto C. S.
Abstract: Memantine is a drug approved for the treatment of moderate‐to‐severe Alzheimer's disease (AD), and there is ongoing research on the potential expansion of its clinical applicability. Published data on the pharmacokinetics of memantine in the mouse are still incomplete, particularly for chronic administration regimens and mouse models of specific genetic disorders. Down's syndrome (DS) is a genetic disorder known to affect multiple organs and systems, with the potential to alter significantly drug pharmacokinetics. Here, we describe a simple, efficient and sensitive GC/MS‐based procedure for the determination of memantine concentrations in murine blood and tissue samples. We analysed pharmacokinetic properties of memantine, particularly its distribution in blood, brain and liver in the Ts65Dn mouse model of DS and euploid F1 hybrid mice after single intraperitoneal administrations of increasing doses of this drug. We also determined steady‐state memantine concentrations in plasma, brain and liver after chronic oral administration of this drug in adult male Ts65Dn mice, euploid littermate controls and nursing or pregnant Ts65Dn mice. Our results revalidated the acute dose of memantine used in previously published work, determined the appropriate amount of memantine to be mixed into mouse chow to achieve steady and pharmacologically relevant plasma and tissue levels of this drug and demonstrated that memantine can be transferred from mother to offspring via maternal milk and placenta. Most of these findings are potentially applicable not only to the study of DS but also to other neurodevelopmental and neurodegenerative disorders.